A comparative analysis of brazilian strategic planning in the 90S: A study of projects of urban promotion of ippuc, the 'rio cidade program' and the 'tamanduatehy axle' - Pasquotto, Geise Brizotti; Retto, Adalberto da Silva [UNESP] (My University, 2007)
The present work proposes a comparative analysis of three Brazilian strategic planning experiments from the 1990s. The chosen urban interventions are the 'Rio Cidade' Program (Rio de Janeiro), the 'Tamanduatehy Axis' (São Paulo) and the IPPUC projects (Paraná), that are inserted in the beggining of the international urban debate. From this study on, this paper seeks a critical analysis of the present urban processes and the utilization of new tools to promote cities.
Keywords: Cities and urban design; Strategic planning; Urban interventions; Urban marketing